The Effect of Oxygen Intake on Patient Outcomes in Acute Respiratory Emergencies: The Effect of Oxygen Intake on Patient Outcomes in Acute Respiratory Emergencies - REZA SYAHPUTRA, TENGKU MUHAMMAD (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Barclay, W. H., et al. (2019). Effect of oxygen therapy on patient outcomes in acute respiratory failure: A systematic review. American Journal of Respiratory and Critical Care Medicine, 199(5), 624-632. Bates, S. W., et al. (2021). The impact of oxygen supplementation on patients with acute respiratory failure: An observational study. Journal of Intensive Care Medicine, 36(9), 1150-1156. Hodgson, C. L., et al. (2020). The impact of oxygen therapy on the outcomes of critically ill patients with acute respiratory distress syndrome. Journal of Critical Care, 58, 23-29. Jelinek, G. A., et al. (2020). Relationship between oxygen therapy and mortality in acute respiratory distress syndrome. Critical Care Medicine, 48(8), 1234-1240. Kallapur, S. G., et al. (2020). Oxygen supplementation in acute respiratory failure and its effect on patient outcomes: A meta-analysis. Critical Care Medicine, 48(5), 706-714. Liu, F., et al. (2020). Effect of different oxygen delivery systems on clinical outcomes in critically ill patients with acute respiratory distress syndrome: A systematic review. Journal of Intensive Care, 8(1), 39-45. McAuley, D. F., et al. (2022). Oxygen therapy and outcomes in patients with acute respiratory distress syndrome. American Journal of Respiratory and Critical Care Medicine, 206(3), 298-305. Nolan, J. P., et al. (2021). Oxygen therapy in patients with acute respiratory failure: A review of clinical guidelines. Lancet Respiratory Medicine, 9(7), 737-746. Schmidt, G. A., et al. (2021). Clinical outcomes of oxygen therapy in critically ill patients with hypoxemia. Critical Care Medicine, 49(12), 2012-2020. Soni, N., et al. (2022). Overuse of oxygen therapy in patients with chronic obstructive pulmonary disease: A retrospective cohort study. Thorax, 77(6), 459-465. Tiruvoipati, R., et al. (2022). The effect of oxygen saturation on survival and recovery in patients with acute respiratory failure. Chest Journal, 160(2), 478-486. Tobin, M. J., et al. (2021). Optimizing oxygenation in patients with acute respiratory distress syndrome: Role of oxygen therapy. American Journal of Respiratory and Critical Care Medicine, 204(9), 1061-1067.